Burden of bacterial antimicrobial resistance among hospitalised patients in Spain: findings from three nationwide prospective studiesResearch in context - Germán Peñalva; Rafael Cantón; María Teresa Pérez-Rodríguez; Juan José González-López; Jesús Rodríguez-Baño; Ester del Barrio-Tofiño; Cristina Kirkegaard-Biosca; Isabel Sánchez-Romero; Andrea Gutiérrez-Villanueva; Teresa Marrodán-Ciordia; José Manuel Guerra-Laso; Cristóbal del Rosario-Quintana; et al. (The Lancet Regional Health. Europe)
Summary: Background: Assessing the burden of antimicrobial resistance is essential to determine the magnitude of this problem and to set its priority. We aimed to estimate the burden of disease caused by multidrug-resistant microorganisms (MDRO) in hospitalised patients in Spain. Methods: Three prospective nationwide studies were conducted in 2018, 2019 and 2023. All patients with a new diagnosis of infection with any of 10 selected MDROs plus Clostridioides difficile during the study period (one week in 2018 and 2019 and two weeks in 2023) were included. Patient demographic, and clinical outcomes were analysed, including incidence, crude all-cause 30-day mortality and years of life lost (YLL). These results were used to calculate weighted and seasonally adjusted annual estimates for the whole country. Findings: In total, 82, 133 and 130 centres participated in the study in 2018, 2019 and 2023, respectively, recording a total of 907, 1392 and 2351 MDRO infections, representing a weighted incidence density of 3.54 (95% CI 2.92–4.17), 5.01 (3.95–6.07), and 4.41 (3.55–5.27) cases/1000 stays, respectively. A total of 161, 198 and 352 patients died with an MDRO infection, representing a weighted incidence density of 0.46 (0.16–0.76), 0.43 (0.17–0.69), and 0.62 (0.52–0.72) deaths/1000 stays, respectively. Based on these data, a nationwide occurrence of 155,294 MDRO infections (95% CI 127,928–182,569) with 20,065 deaths (6938–32,958) was estimated for 2018, 210,451 MDRO infections (165,963–254,975) with 17,982 deaths (7071–28,700) for 2019, and 173,653 MDRO infections (139,814–207258) with 24,582 deaths (20,461–28,796) for 2023. Interpretation: The burden of disease caused by MDRO infections among hospitalised patients in Spain is very high and remains stable over the study period. National actions to combat bacterial resistance need to be intensified. Funding: The management costs of this study were funded by the Spanish Society of Infectious Diseases and Clinical Microbiology (SEIMC). Researchers have participated voluntarily and none of the investigators received funding for conducting the study.